Berberine as a Modulator of Metabolic and Hormonal Dysregulation in PCOS: Mechanisms of Action and Clinical Implications - A Narrative Review - Buczkowska, Ewa; Marciszewska, Aleksandra; Piechowicz, Agnieszka; Popczyk, Natalia; Przybyłowska, Agnieszka; Jopek, Jakub; Popczyk, Michał; Bryksy, Sylwia; Tymchenko, Hanna; Kaźmierczyk, Jakub (Quality in Sport, 2026)
Background. Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age and is a leading cause of anovulatory infertility. Its pathogenesis is considered multifactorial, involving polygenic susceptibility, environmental influences, and possible epigenetic modifications, although no definitive etiological trigger has been identified and no validated genetic screening is currently recommended. PCOS is associated with significantly reduced quality of life due to both metabolic and hyperandrogenic features, with diagnostic criteria remaining based on the Rotterdam framework. Materials and methods. An extensive literature review was conducted using sources retrieved from the PubMed and Google Scholar databases. Aim. The aim of this study was to analyze and synthesize the current body of evidence on polycystic ovary syndrome (PCOS), with a particular focus on evaluating the role of non-pharmacological interventions, especially berberine supplementation. Conclusions. Berberine exhibits pleiotropic benefits in women with PCOS, improving insulin sensitivity, glycemic control, and lipid profiles through modulation of key metabolic pathways. It also demonstrates antiandrogenic effects by reducing free testosterone and increasing SHBG levels, contributing to improved hormonal balance and reproductive function. Overall, berberine appears to be a promising and well-tolerated adjunct or alternative therapy, although further high-quality studies are needed to confirm its long-term efficacy and impact on reproductive outcomes.